Three-dimensional coded aperture scintigraphy proposed for early tumor detection - Hussain, K.; Saripan, M.I.; Alnafea, M.A.; Mahboub, D.; Mahmud, R.; Adnan, W.A. Wan; Xianling, D. (Novin Medical Radiation Institute, 2024)
Background: Modified Uniformly Redundant Array (MURA) Coded Aperture (CA) is a type of mask recently proposed for breast tumor imaging. Such masks have been frequently used in nuclear medicine clinical applications for the past two decades. All CA imaging methods are still limited to planar imaging, with only a few exceptions where they can be used for thin 3D imaging. At present, there is no commercially available SPECT camera that employs CA technology. Materials and Methods: This paper is investigating the proof-of-concept of the MURA CA mask for 3D breast tumor imaging. Such image formation performed well in planar imaging, but it is not fully evaluated for thick sources in 3D imaging. This paper demonstrated the performance of MURA in 3D breast imaging. The proposed imaging system uses a MURA mask and antimask dual reconstruction, and the raw projections are reconstructed using an iterative algorithm, Maximum Likelihood Expectation Maximization (MLEM). Results: The MURA antimask-reconstructed images are summed with mask images to enhance sensitivity, and the resultant image with up to 3 mm lesion diameter can be detected. The reconstructed image quality is measured by plotting profiles and by measuring contrast-to-background ratio, peak-signal-to-noise ratio, and mean square error. Conclusion: The proposed scintigraphy system has successfully reconstructed a breast phantom with a lesion of 3 mm diameter and tumor-to-background ratio of 10:1 using a MURA CA mask. Therefore, MURA 3D scintigraphy can be used to diagnose cancer at an early stage.